2010
DOI: 10.1080/09540120903483018
|View full text |Cite
|
Sign up to set email alerts
|

Poor health-related quality of life and abnormal psychosocial adjustment in Italian children with perinatal HIV infection receiving highly active antiretroviral treatment

Abstract: To evaluate health-related quality of life (HRQL), social competence, and behavioral problems in children with perinatal HIV infection receiving highly active antiretroviral therapy (HAART), a cross-sectional study was performed at the Department of Pediatrics, University of Brescia. We evaluated HRQL, social competence, and behavioral problems in 27 HIV-infected children compared with age and sex-matched control subjects using the Pediatric Quality of Life Inventory (PedsQL) and the Child Behavior Checklist (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 21 publications
3
46
0
5
Order By: Relevance
“…The majority of QOL reports in HIV-infected children were from resource-rich settings, and conducted as cross-sectional studies in children already treated with ART. 3,[10][11][12] There are limited data of QOL change before and after ART initiation in HIV-infected children without AIDS symptoms. 13 Our team has conducted a multicenter, randomized, openlabel study of early versus deferred ART among Thai and Cambodian ART-naĂŻve HIV-infected children with CD4 15-24% (Pediatric Randomized of Early vs.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of QOL reports in HIV-infected children were from resource-rich settings, and conducted as cross-sectional studies in children already treated with ART. 3,[10][11][12] There are limited data of QOL change before and after ART initiation in HIV-infected children without AIDS symptoms. 13 Our team has conducted a multicenter, randomized, openlabel study of early versus deferred ART among Thai and Cambodian ART-naĂŻve HIV-infected children with CD4 15-24% (Pediatric Randomized of Early vs.…”
Section: Introductionmentioning
confidence: 99%
“…4 Even though the survival was prolonged by ART there are at risk of impaired psychosocial functioning as their lower scores on total competence in youth (11-18 years) self report. 9 In contrast a quality of life study conducted among Indian children revealed that they have a better psychosocial and school functioning scores than children with cystic fibrosis 5 HIV children with normal CD4 count and undetectable viral load had school (51%) and dropout (28.6%), 10 they have compromised executive function and information processing, 11 81% systematic review reported some form of cognitive delay.…”
Section: Discussionmentioning
confidence: 99%
“…3 The quality of life assessment studies among the children with HIV infection showed that their physical, psychosocial and school functioning was affected. [4][5][6] People living with AIDS and cancer experience stress, stress influences the number of immune cells and cytokine dysregulation. The practice of yoga, meditation, muscle relaxation, hypnosis was shown the effect of reducing the psychological and physiological effect of stress in cancers and HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that children and adolescents with HIV infection were at increased risks of psychological and behavioral problems [9,10]. In a cohort study, emotional and behavioral problems were found in 24.5% of HIV-infected adolescents [11].…”
Section: Introductionmentioning
confidence: 95%